2017
DOI: 10.1097/inf.0000000000001527
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cytomegalovirus Infection and Permanent Hearing Loss in Rural North Indian Children

Abstract: Background Congenital cytomegalovirus infection (cCMV) is a leading non-genetic cause of permanent congenital or early-onset hearing loss (PCEHL). Although cCMV rates are high despite near-universal seroimmunity, the contribution of cCMV to PCEHL in the developing world is unclear. Methods Neonates at a rural north Indian hospital were screened for cCMV by saliva PCR and hearing by distortion product otoacoustic emission (DPOAE) testing. CMV positive infants and those not passing newborn hearing screening (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…A total of 20 studies, published from 2004 to 2020, were included in this review. These studies were conducted from 1998 to 2018 and reported data on etiology of hearing loss among children who had undergone UNHS in the following countries: Australia, 10,11 Belgium, 12,13 Brazil, 14 China, 15 Croatia, 16 India, 17 Ireland, 18 Israel, 19 Italy, 20 Japan, 21 Norway, 22 Taiwan, 23,24 United Kingdom, 25 and the United States 26-29 ( Table 1 ). Altogether, the 20 studies included 2149 children with congenital hearing loss, of which 1787 (83.2%) had etiologic investigation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 20 studies, published from 2004 to 2020, were included in this review. These studies were conducted from 1998 to 2018 and reported data on etiology of hearing loss among children who had undergone UNHS in the following countries: Australia, 10,11 Belgium, 12,13 Brazil, 14 China, 15 Croatia, 16 India, 17 Ireland, 18 Israel, 19 Italy, 20 Japan, 21 Norway, 22 Taiwan, 23,24 United Kingdom, 25 and the United States 26-29 ( Table 1 ). Altogether, the 20 studies included 2149 children with congenital hearing loss, of which 1787 (83.2%) had etiologic investigation.…”
Section: Resultsmentioning
confidence: 99%
“…12,24 The prevalence of congenital hearing loss ranged from 1.0 to 6.4 per 1000 newborns screened. 17,22 The number of children diagnosed with hearing loss ranged from 6 to 548 ( Table 2 ). 15,24 The proportion of those who had an etiologic investigation ranged from 23% 27 to 100% in 13 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural history of congenital CMV infection in LMIC has not been well defined except for the data from prospective newborn screening studies in Brazil. These studies demonstrate that the prevalence of CMV-associated hearing loss is similar to that seen in the U.S. and northern Europe [18], [19]. The frequency and severity of other neurodevelopmental sequelae in these populations have not been well characterized.…”
Section: Congenital CMV Disease Burden In Low- and Middle-income Counmentioning
confidence: 79%
“…A number of studies in populations in resource-limited settings over the past decade have demonstrated that congenital CMV infection is an important cause of childhood morbidity [6], [7], [17], [18], [19]. As a higher prevalence of congenital CMV infection is seen in populations with high and often near-universal seroimmunity, a substantial number of infants born in the LMICs are CMV-infected.…”
Section: Congenital CMV Disease Burden In Low- and Middle-income Counmentioning
confidence: 99%